Occupational Safety and the Shift from Common to Individual Fishing Quotas in the Gulf of Mexico. - Marvasti, Akbar; Dakhliaf, Sami (Southern Economic Journal, 2017)
We investigate and measure how a shift from a regime of common property to one of private ownership of fishing rights affected the safety of commercial fishing activity. To deal with overfishing and stock depletion of red snapper and grouper-tilefish in the Gulf of Mexico (GOM), various regulatory controls, most notably common quotas and seasonal closures, were introduced in the early 1990s. The resulting 'fishing derbies' led to an increased number of accidents and fatalities. We show that the subsequently implemented individual fishing quota programs led to a sharp reduction in the number of fatalities, in large part because of lower pressure to make risky trip decisions, in particular under adverse weather conditions.